2022
DOI: 10.3390/jcm11175236
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Distress among Family Members of COVID-19 Patients Admitted to Hospital and Isolation Facilities in the Philippines: A Prospective Cohort Study

Abstract: This study determined the psychosocial impact of COVID-19 on families of adult COVID-19 patients in isolation facilities in Metro Manila, Philippines. This prospective cohort study was conducted in COVID-19 healthcare facilities. Data collection was undertaken 2 weeks and 8 weeks after discharge. Logistic regression was performed to determine the socioeconomic and clinical factors influencing anxiety, depression, and family function. Based on HADS-P, 43.2% of the participants had anxiety symptoms, and 16.2% ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This might have aggravated the already existing perceptions of stigma experienced by people in higher socioeconomic status. In the case of this analysis, risk aversion may be related to the risk of psychosocial and mental costs of stigmatization associated with having a family member diagnosed or isolated in a facility [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might have aggravated the already existing perceptions of stigma experienced by people in higher socioeconomic status. In the case of this analysis, risk aversion may be related to the risk of psychosocial and mental costs of stigmatization associated with having a family member diagnosed or isolated in a facility [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instrumen ini adalah kuesioner yang berisi keenam domain SCREEM (Social, Cultural, Religious, Educational, Econimic, Medical). [12] Tabel 2. Pengisian Family SCREEM pada Family Folder pasien DM Tipe II…”
Section: Gambar 4 Family Map Pasien Dm Tipe II C Apgar Keluarga (Fami...unclassified
“…Both female gender and the persistence of symptoms were risk factors in developing psychological distress among COVID-19 survivors 9 months after discharge [10]. Moreover, a study among COVID-19 survivors in the Philippines found that the prevalence of anxiety and depression 8 weeks after discharge were significantly reduced [11]. However, the available evidence regarding long-term psychological distress among COVID-19 survivors is still insufficient.…”
Section: Introductionmentioning
confidence: 99%